Social media usage and acceptance in higher education: A structural equation model - Al-Rahmi, Ali Mugahed; Shamsuddin, Alina; Wahab, Eta; Al-Rahmi, Waleed Mugahed; Alismaiel, Omar A.; Crawford, Joseph (Frontiers in Education, 2022)
The adoption and use of social media as an educational technology in higher education has been exacerbated during the COVID-19 pandemic. As a result, this study applied the unified theory of usage and acceptance of technology theory and the technology acceptance model as predictors of behavioral intention to use social media and actual social media use. These, as posited by the model, affect the performance impact of social media usage. This study involved a quantitative survey with 312 undergraduate university students in Malaysia. Using structural equation modelling, this study identified that unified theory of usage and acceptance of technology theory and the technology acceptance model influence behavioral intentions to use and actual use of social media, resulting in an improved performance impact. That is, when students see the value in particular technologies, feel their performance (e.g., passing their studies) will be improved by using that technology, offers behavioural nudges towards adoption and use